A microemulsion co-loaded with Schizandrin A–docetaxel enhances esophageal carcinoma treatment through overcoming multidrug resistance. (1st January 2017) - Su, Xiangyu; Gao, Chanchan; Shi, Fangfang; Feng, Xiaoyao; Liu, Lin; Qu, Ding; Wang, Cailian
Abstract: Multidrug resistance (MDR) is the major underlying cause of the low 5-year survival rate of esophageal carcinoma. In this study, we developed a novel microemulsion system (SD-ME) co-loaded with docetaxel (DTX) and Schizandrin A, a potent chemotherapeutic agent and a potential drug resistance modulator, respectively. In the physicochemical characterization studies, SD-ME displayed a well-defined spherical shape and size (56.62 ± 4.16 nm), a narrow polydispersity index (PDI, 0.132 ± 0.002), and a negative surface charge (−19.81 ± 3.11 mv). In the cellular uptake studies, SD-ME with a DTX concentration of 30 μg/mL exhibited a 3.9-fold enhancement of DTX internalization in DTX-resistant EC109 (EC109/DDR) cells in comparison to that observed for EC109 cells, and the mechanisms were associated with reducing P-gp expression and inhibiting P-gp ATPease. The half-maximal inhibitory concentrations (IC50 ) of DTX and SD-ME against EC109/DDR cells were 40.57 ± 0.39 and 3.59 ± 0.06 μg/mL, respectively. Likewise, the apoptotic rate of EC109/DDR treated with SD-ME increased up to 20-fold compared to that observed with free DTX. In anticancer efficacy studies in vivo, SD-ME markedly retarded the tumor growth of nude mice bearing EC109/DDR tumor xenografts compared with D-ME and free DTX throughout the duration of study. Consequently, mice treated with SD-ME had the highest survival rate (37.5%) during the observation period (70 days). In addition, there were no apparent side effects after the administration of SD-ME. Overall, our study provides evidence for SD-ME as an effective drug delivery system for enhanced MDR tumor treatment.